2016
DOI: 10.1108/ajems-10-2015-0121
|View full text |Cite
|
Sign up to set email alerts
|

Perceived experience value, satisfaction and behavioural intentions

Abstract: Purpose Globally, guesthouses provide an important source of accommodation to visitors and tourists. Surprisingly, research into this sector is rather sparse. The purpose of this paper is to examine the dimensions of experience value, determine guests’ perceptions of experience value, analyse the influences of various profile variables on experience value, and investigate the relationship between experience value, satisfaction, and customer behavioural intentions regarding guesthouses in Ghana. Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 52 publications
1
31
0
4
Order By: Relevance
“…Bilgihan (2016) Online marketing is expected to be different as they process website information five times faster than older generations and are the most emotional and least loyal customers as compared to all other generations in providing customer experiences Bilgihan, Kandampully, and Zhang (2016) Online shopping environment is dynamic because consumers connections with e-vendors, researchers and professionals that are important for understanding and that create a compelling online user experience Stein and Ramaseshan (2016) Customer experience elements like touch points, which include; atmospheric, technological, communicative, process, employee-customer interaction, customercustomer interaction and product interaction elements are most important Amoah et al (2016) Customer experience strategy that can enhance customer satisfaction, positive behavioral intentions, growth, and sustainability Rukhsana Gul Gilal (2016) The self-concept emerged as a stronger driver for brand experience and consumer brand relationship, then for brand preference and customer satisfaction Sun (2002) Customer experience helps marketers in establishing powerful Brand awareness, brand association, perceived quality, and brand Loyalty…”
Section: Prior Studies On Customer Experience References Key Pointsmentioning
confidence: 99%
“…Bilgihan (2016) Online marketing is expected to be different as they process website information five times faster than older generations and are the most emotional and least loyal customers as compared to all other generations in providing customer experiences Bilgihan, Kandampully, and Zhang (2016) Online shopping environment is dynamic because consumers connections with e-vendors, researchers and professionals that are important for understanding and that create a compelling online user experience Stein and Ramaseshan (2016) Customer experience elements like touch points, which include; atmospheric, technological, communicative, process, employee-customer interaction, customercustomer interaction and product interaction elements are most important Amoah et al (2016) Customer experience strategy that can enhance customer satisfaction, positive behavioral intentions, growth, and sustainability Rukhsana Gul Gilal (2016) The self-concept emerged as a stronger driver for brand experience and consumer brand relationship, then for brand preference and customer satisfaction Sun (2002) Customer experience helps marketers in establishing powerful Brand awareness, brand association, perceived quality, and brand Loyalty…”
Section: Prior Studies On Customer Experience References Key Pointsmentioning
confidence: 99%
“…In tourism context, revisit purchase, sharing positive experience, and spreading positive publicity are the greatest importance for the tourism industry and a key element of many firms' Besides repurchase behaviour, loyal tourists create positive word of mouth publicity (WOM) and it is the most powerful influence for the purchasing decision of the potential tourists. Supported that loyalty is a significant antecedent of behavioural intention such as saying positive things about the business or called as "word-ofmouth (WOM)" (Amoah, Radder, Eyk and van Eyk, 2016;Harris and Khatami, 2017) it is the most powerful influence for the purchasing decision of the potential tourists. Thus, tourist loyalty will be shown through many ways, such as revisiting, recommendation, and positive word of mouth publicity (Gnanapala, 2015).…”
Section: Tourist Loyaltymentioning
confidence: 99%
“…Previous studies found that tourist loyalty as an outcome was affected positively by tourist satisfaction. Therefore, when customer satisfaction increases, lead to intention to return and recommend to other rises, whereby significant for customer loyalty (Amoah et al, 2016;Chiu et al, 2016;Liang, 2008;Wahyuningsih, 2012). As Kotler et al (2017) stated the customer loyalty drives to continue to use the same product or service, able to reduce cost of promotional, decreased the price sensitivity.…”
Section: Competitive Advantage Through Tourist Satisfaction and Loyaltymentioning
confidence: 99%
“…Guest houses present an alternative to the traditional hotels and are gaining increasing attention in tourism studies. Existing literature has identified some main characteristics of guest houses, focused on two types: the first type is on the traditional salient attributes, including comfort of bed, privacy, cleanliness [20], economic value [25], location [18], efficiency [26], facilities, and employees' empathy [13,26]; the second type contains items concerned with tourists' engagement with remote destinations, such as the unique characteristics of guest houses compared with regular hotels (e.g., the sense of home and exotic local culture) [20]. Exotic local culture is one significant indicator affecting tourists' pursuit and experience in guest houses in remote destinations [21].…”
Section: Relationship Between Tourist Perception Of Exotic Local Cultmentioning
confidence: 99%